2008
DOI: 10.1001/jama.299.21.2515
|View full text |Cite
|
Sign up to set email alerts
|

Association of Family History With Cancer Recurrence and Survival Among Patients With Stage III Colon Cancer

Abstract: PPROXIMATELY 16% TO 20% of patients with colorectal cancer have a first-degree relative with colorectal cancer. 1 Beyond rare but highly penetrant hereditary colorectal cancer syndromes, numerous studies have demonstrated that a history of colorectal cancer in a first-degree relative increases the risk of developing the disease by approximately 2-fold. [2][3][4][5] However, the influence of family history on cancer recurrence and survival among patients with established colon cancer remains uncertain. A study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
73
4
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 29 publications
11
73
4
2
Order By: Relevance
“…The percentage of the studied cases with CRC with a positive family history was 21.7 %. This comes in agreement with (26,27) who told a percentage of up to 20 %.…”
Section: Discussionsupporting
confidence: 88%
“…The percentage of the studied cases with CRC with a positive family history was 21.7 %. This comes in agreement with (26,27) who told a percentage of up to 20 %.…”
Section: Discussionsupporting
confidence: 88%
“…Similar studies reported a significant association between neoplastic prognosis and positive family history, which found better prognosis in breast cancer, colon cancer and gastric cancer [15][16][17][18]. In addition, the high incidence of NPC among Southern Chinese and population of Southern Chinese descent suggest a component of genetic susceptibility, and genetic factor may play an important role in tumorigenesis of NPC.…”
Section: Introductionmentioning
confidence: 63%
“…As recommended by the American Society of Clinical Oncology, the adjuvant therapy for patients with stage II colon cancer could be applied to patients with inadequately sampled nodes, T4 lesions, perforation, and poorly differentiated histology (38). Besides, other high-risk factors such as lymph, vascular, or perineural invasion; close, indeterminate, or positive margins; bowel obstruction; BMI; and family history are also known to bring higher rate of recurrence, and adjuvant chemotherapy should be considered in this population (39)(40)(41). We are still unable, for example, to separate the 20% of node-negative patients who will relapse from the 80% who will not; as a result, many patients receive unnecessary adjuvant treatment, which might be harmful, and many receive inadequate treatment, leading to overtreatment or undertreatment of many patients with adjuvant therapies.…”
Section: Discussionmentioning
confidence: 99%